Infinite servers queue systems busy period - a practical case on logistics problems solving - Filipe, J. A.; Ferreira, M. A. M. (Applied Mathematical Sciences, 2015)
In this paper it is exemplified how the busy period of an infinite servers queue is applied to the equipments failures management. With this model it is possible to obtain system performance measures and also to contribute to solve organizing structures’ problems, by minimizing the risks of the organizations inoperative structures, with considerable logistics pernicious consequences for companies and often also for the regions where the companies are inserted